5-Fluorouracil Response Prediction and Blood Level–Guided Therapy in Oncology: Existing Evidence Fundamentally Supports Instigation. Issue 5 (October 2020) - Chavani, Ottiniel
Abstract: 5-Fluorouracil (5-FU) response prediction and therapeutic drug monitoring (TDM) are required to minimize toxicity while preserving efficacy. Conventional 5-FU dose normalization uses body surface area. It is characterized by up to 100-fold interindividual variability of pharmacokinetic (PK) parameters, and typically >50% of patients have plasma 5-FU concentrations outside the optimal range. This underscores the need for a different dose rationalization paradigm, hence there is a case for 5-FU TDM. An association between 5-FU PK parameters and efficacy/toxicity has been established. It is believed that 5-FU response is enhanced and toxicity is reduced by PK management of its dosing. The area under the concentration–time curve is the most relevant PK parameter associated with 5-FU efficacy/toxicity, and optimal therapeutic windows have been proposed. Currently, there is no universally applied a priori test for predicting 5-FU response and identifying individuals with an elevated risk of toxicity. The following two-step strategy: prediction of response/toxicity and TDM for subsequent doses seems plausible. Approximately 80% of 5-FU is degraded in a three-step sequential metabolic pathway. Dihydropyrimidine dehydrogenase (DPD) is the initial and rate-limiting enzyme. Its deficiency can cause toxicity with standard 5-FU doses. DPD also metabolizes uracil (U) into 5, 6-dihydrouracil (UH2 ). The UH2 /U ratio is an index of DPD activity and a credible biomarker of response and toxicity. This article outlines the UH2 /U ratio as a parameter for 5-FU response/toxicity prediction and highlights key studies emphasizing the value of 5-FU TDM. Broad application of 5-FU response/toxicity prediction and blood level–guided therapy remains unmet, despite ever-increasing clinical interest. Considered collectively, existing evidence is compelling and fundamentally supports universal instigation of response/toxicity prediction and TDM.